Analysis of the Relationship Between Implementation and Policy for Regional-Scale Waste Management in Garut District - Maulana, Suhenra (Engineering, MAthematics and Computer Science Journal (EMACS), 2025)
Waste management is currently still a big challenge for all cities/regencies in Indonesia where there is still a lot of household waste that has not been managed and still relies on open dumping. This study aims to determine the relationship between the existence of a policy for the provision of regional-scale Waste Treatment Facilities with TPS 3R and its implementation in each village/sub-district in Garut District. The research method used is quantitative, and the data analysis used in this study is explanatory research which aims to explain whether or not there is a relationship between the independent variables, namely knowing the regent's instruction letter regarding the provision of regional-scale Waste Treatment Facilities with TPS 3R. The process of analyzing research data using the Fisher's Exact Test statistical test shows that the p-value is 0.158. Based on the applicable provisions, if the p-value is smaller than the significance level (α = 0.05) then H_0 (null hypothesis) is rejected and H_1 (alternative hypothesis) is accepted. Therefore, it was found that the p-value is greater than the significance level (0.158 > 0.05) then H_0 is accepted, which means that there is no statistically significant relationship between knowing the policy of providing regional-scale Waste Treatment Facilities with TPS 3R with the implementation of the provision of waste treatment facilities. This means that knowledge of the existence of policies through the regent's instruction letter does not have a significant effect on the implementation of waste treatment in villages/sub-district areas, this could mean that there are other factors that have a greater influence on the implementation of waste treatment in villages/sub-districts.